Development and psychometric properties of the maternal ambivalence scale in spanish women - Magdalena Belén Martín-Sánchez; Verónica Martínez-Borba; Patricia Catalá; Jorge Osma; Cecilia Peñacoba-Puente; Carlos Suso-Ribera (BMC, 2022)
Abstract Background maternal ambivalence, which refers to experiencing mixed emotions about motherhood, like happiness and sadness, is frequent during the perinatal period. Aim Due to the relevance of this topic and the lack of psychometrically-sound instruments to measure it, this study aims to develop and test a measure of maternal ambivalence called the Maternal Ambivalence Scale (MAS). Methods in this cross-sectional, observational study, participants were 1424 Spanish women recruited online who were either pregnant (33%) or recent mothers of children under 2 years (67%). They responded to the MAS and measures of anxiety and depressive symptoms and life satisfaction. Analyses included exploratory and confirmatory factor solutions for the MAS, internal consistency estimates (Cronbach's α) for all scales, as well as bivariate correlations to investigate sources of validity evidence. Comparisons between pregnant and postpartum women were also examined. Results The assumptions for factor analysis about the relationship between items were met (Kaiser-Meyer-Olkin's [KMO] test = 0.90; Barlett's Chi-square sphericity test = 5853.89, p < .001). A three-factor solution (Doubts, Rejection, and Suppression) for the MAS showed a good model fit both in exploratory (Chi-square = 274.6, p < .001, Root Mean Square Error of Approximation [RMSEA] = 0.059, RMSEA 90% Confidence Interval [CI]=[0.052, 0.066], Comparative Fit Index [CFI] = 0.985, Tucker Lewis Index [TLI] = 0.974) and confirmatory analyses (Chi-square = 428.0, p < .001, RMSEA = 0.062, RMSEA 90% CI=[0.056, 0.068], CFI = 0.977, TLI = 0.971). Doubts (α = 0.83), Rejection (α = 0.70), and Suppression (α = 80) were associated with higher anxiety and depressive symptoms, as well as lower life satisfaction (all p < .001). Pregnant women presented greater Rejection (mean difference = 0.30, p = .037, 95% CI=[0.02, 0.58]) and less Suppression (mean difference=-0.47, p = .002, 95% CI=[-0.77,-0.17]) than mothers. Conclusion with this study, we provide clinicians and researchers with a novel tool that successfully captures the complex nature of maternal ambivalence. Given the associations of maternal ambivalence with important outcomes in perinatal women, this tool could be important for the prevention of distress associated with chronic ambivalence and to evaluate the effectiveness of interventions addressing ambivalence.